2007
DOI: 10.1097/psy.0b013e3180f6171f
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Dispositional Mindfulness During Affect Labeling

Abstract: Objective: Mindfulness is a process whereby one is aware and receptive to present moment experiences. Although mindfulnessenhancing interventions reduce pathological mental and physical health symptoms across a wide variety of conditions and diseases, the mechanisms underlying these effects remain unknown. Converging evidence from the mindfulness and neuroscience literature suggests that labeling affect may be one mechanism for these effects. Methods: Participants (n ϭ 27) indicated trait levels of mindfulness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
426
2
18

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 681 publications
(476 citation statements)
references
References 21 publications
30
426
2
18
Order By: Relevance
“…The location of sustained activation is consistent with previous studies that reported a significant correlation between MedPFC activation and rumination (Ray et al, 2005) and MedPFC activation and mindfulness (Creswell et al, 2007). A whole-brain analysis utilizing the same threshold did not identify any other regions of the brain to display this pattern.…”
Section: Discussionsupporting
confidence: 89%
“…The location of sustained activation is consistent with previous studies that reported a significant correlation between MedPFC activation and rumination (Ray et al, 2005) and MedPFC activation and mindfulness (Creswell et al, 2007). A whole-brain analysis utilizing the same threshold did not identify any other regions of the brain to display this pattern.…”
Section: Discussionsupporting
confidence: 89%
“…Emotionintrospection activated more posteriorly bilateral inferior frontal/premotor regions and also minor parts of the middle insula. This was not fully in line with findings of activity in the relatively more anterior VLPFC during affect labeling in states of mindfulness (Brefczynski-Lewis et al, 2007;Creswell et al, 2007;Farb et al, 2007;Lieberman et al, 2007;Stein et al, 2008) but in part with interoception associated activity in the insula (Critchley et al, 2004).…”
Section: Self-referencementioning
confidence: 69%
“…Ventrolateral prefrontal and midline prefrontal areas and also the amygdala were identified to be important components of mindfulness mediating networks (Brefczynski-Lewis et al, 2007;Creswell et al, 2007;Farb et al, 2007;Stein et al, 2008).…”
Section: Emotion Introspection and Clinical Implicationsmentioning
confidence: 99%
“…Further, subjects with higher trait mindfulness scores showed greater prefrontal and less amygdala activity during affect labeling (Creswell et al, 2007). Another study used the mindfulness-related construct 'level of emotional awareness' and found similar positive correlations between level of emotional awareness and activation in response to emotional stimuli in prefrontal, cingulate and insular cortex .…”
Section: Introductionmentioning
confidence: 82%
“…Resulting summary images were subjected to second-level group analyses within predefined cubic ROIs: in our main ROI, the amygdala (Figure 2), and additionally in the DMPFC, DLPFC and anterior insula. ROIs were defined according to activation coordinates in fMRI studies on emotion regulation (amygdala; Ochsner et al, 2002;Ochsner et al, 2004;Goldin et al, 2008;Herwig et al, 2010) and studies on mindfulness (anterior insula, DMPFC, DLPFC; Creswell et al, 2007;Herwig et al, 2010) and anatomically validated using the Talairach client (Lancaster et al, 2000). MNI coordinates were non-linearly transformed into TAL space with Matlab's mni2tal-function (Brett, 2009).…”
Section: Fmri Acquisitionmentioning
confidence: 99%